A survey-based study on awareness of eye diseases among population of Bangladesh - Nasrin, Nishat; Asaduzzaman, Muhammad; Sharmin, Dilruba; Tithi, Nigar Sultana; Hudda, Syed Md Nazmul (Asian Journal of Medical and Biological Research, 2020)
Awareness of common eye diseases and their early detection can play a vital role in encouraging people to seek timely eye care and therefore help in reducing the burden of visual impairment. This study was designed to reveal the assessment of awareness of eye diseases among the population of Bangladesh in different locations. For this, a total of 750 respondents were selected by convenient sampling and were interviewed using a structured questionnaire. From this study, we found that only 50% of the respondents were aware of glaucoma and only 35% had knowledge about glaucoma. About 52% of the study population was aware of cataract and 19% of them had knowledge that the risk of cataract increases by getting older. About 38% of the participants had an understanding of night blindness. Diabetes can lead to eye diseases and this was known to 40% of the study population. Only 23% of the respondents were concern about their family’s present eye health condition. Frequency of taking nutritional food for optimum health was very poor. Daily nutritional foods were taken by 17% of the participants. About 36% of study subjects maintained their blood pressure and obesity. From our survey results, it can be implied that the level of awareness and knowledge about common eye diseases among the population of Bangladesh was not satisfactory. Highlighting importance to the tertiary eye care, imposing health education and raising awareness will assist to understand the importance of routine eye examination for early detection and treatment of such conditions. Asian J. Med. Biol. Res. June 2019, 5(4): 292-296